Influence of k-wire placement on impact mechanics and bone fracture in a rabbit model of cartilage injury - Hessam Noori-Dokht; Julian Dilley; Abhijit Seetharam; Uma Sankar; Roman M. Natoli; Todd O. McKinley; Diane R. Wagner (PLoS ONE, 2026)
In vivo rabbit models that deliver mechanical impacts to knee cartilage are important for studying injury-induced osteoarthritis, but variability in impact characteristics limit the repeatability of the models. In this study, the mechanical impact load delivered to a cadaveric rabbit posterior medial condyle was characterized, with particular emphasis on the influence of placement of the k-wire that stabilized the joint during impact. K-wire position was not prescribed and varied across specimens (7.85 ± 2.28 mm anterior and 2.61 ± 3.47 mm distal to the impact site) and was treated as a source of variability. Impact parameters and subchondral bone failure metrics were quantified, and their relationship with k-wire placement were evaluated using multiple linear regression. Peak stress, loading rate, impact duration and work were significantly associated with k-wire location in the sagittal plane, with these associations primarily driven by the anterior-posterior position of the k-wire. In contrast, the proximal-distal position was not a significant predictor for individual impact parameters. Consistency of the k-wire placement and resulting impact parameters were also assessed. With effort to reproduce a fixed placement, the coefficients of variation of the impact parameters were less than ~15%, indicating relatively consistent impacts. Additionally, regression analysis indicated that a substantial portion of fracture variability was accounted for by k-wire placement, suggesting that caution must be exercised in positioning the k-wire to prevent fractures. Collectively, these findings indicate that the stiff k-wire alters the compliance of the impacted tissue and influences the characteristics of the mechanical impact load and the susceptibility to subchondral bone fracture. These results highlight the importance of precise joint stabilization in impact-based osteoarthritis models and provide a foundation for future studies on cartilage injury, post-traumatic osteoarthritis disease progression, and novel therapeutic interventions.